Policies on the Move: The Transatlantic Travels of Tax Increment Financing. Issue 2 (3rd March 2016) - Baker, Tom; Cook, Ian R.; McCann, Eugene; Temenos, Cristina; Ward, Kevin
Abstract : Growing influence of the new mobilities paradigm among human geographers has combined with a long and rich disciplinary tradition of studying the movement of things and people. Yet how policy ideas and knowledge are mobilized remains a notably underdeveloped area of inquiry. In this article, we discuss the mobilization of policy ideas and policy models as a particularly powerful type of mobile knowledge. The article examines the burgeoning academic work on policy mobilities and points toward a growing policy mobilities approach in the literature, noting the multidisciplinary conversations behind the approach as well as the key commitments of many of its advocates. This approach is illustrated using the travels of tax increment financing (TIF) with the role of learning and market-making within efforts to introduce TIF in more cities highlighted. In conclusion, we discuss some of the political and practical limits that often confront efforts to mobilize policy ideas.